Selection of Image Repair Strategies in Online Crises: : The Model of Image Repair Selection - M. Klok, Anna-Katrine (Communication & Language at Work, 2024)
In contemporary society, social media plays an ever-increasing role. The frequency and impact of crises, particularly online, are escalating, posing economic and reputational threats to organizations. Although much research on crisis communication and management has emerged, the field still lacks a general theory or paradigm. This research deficiency has reached a point where it is necessary to limit the inclusion of new theoretical elements but instead concretize practical applications of existing theory. Organizations often struggle with inadequate or rhetorically insufficient crisis responses, leading to stakeholder dissatisfaction and subsequently loss of resources. In this article, I have addressed this problem. By examining to what extent, it is possible to create a new theory for selecting an image repair strategy that can be used both during crises and as an analytical tool in retrospect. Thus, proposing a new theory, the Model of Image Repair Selection (MIRS), and proposals for integrating the theory into crisis management efforts, offering practical solutions to the complexity of crises. Thus, this work proposes a new theory, the Model of Image Repair Selection (MIRS), along with recommendations for integrating the theory into crisis management efforts, offering practical solutions to address the complexity of crises. With this, MIRS has the potential to help organizations navigate and lessen the effects of crises. MIRS accommodates both the complex and dynamic dimensions of crises without excluding combinations with other approaches to crisis communication. By integrating the six major rhetorical strategies in crises into a model based on four parameters—risk, transparency, attitude, and communicative resources—MIRS enhances theoretical understanding and provides organizations with a valuable instrument for crisis management